2021
DOI: 10.3389/fmed.2021.753977
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Preclinical PET Imaging Findings: Challenges and Motion Correction to Overcome the Confounding Effect of Anesthetics

Abstract: Preclinical brain positron emission tomography (PET) in animals is performed using anesthesia to avoid movement during the PET scan. In contrast, brain PET scans in humans are typically performed in the awake subject. Anesthesia is therefore one of the principal limitations in the translation of preclinical brain PET to the clinic. This review summarizes the available literature supporting the confounding effect of anesthesia on several PET tracers for neuroscience in preclinical small animal scans. In a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…Different from clinical neuroimaging acquisitions that are performed in awake subjects, small animal in vivo imaging is generally conducted under anesthesia, as restriction of movements is necessary to avoid undesirable artifacts. Anesthesia is therefore one limitation for translational data, as studies in anesthetized animals have reported alterations in brain functioning and connectivity, cerebral blood, and inhibitory GABAergic neurotransmission (Gutierrez‐Barragan et al, 2022; Miranda et al, 2021; Ogawa et al, 2011; Prando et al, 2019). To avoid these limitations, some methodologies have been developed for evaluations in awake‐animals, such as performing scans using devices that restrict movement (Gutierrez‐Barragan et al, 2022; Mizuma et al, 2010; Suzuki et al, 2021) or using motion tracking and motion correction during image reconstruction (Miranda et al, 2019; Spangler‐Bickell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Different from clinical neuroimaging acquisitions that are performed in awake subjects, small animal in vivo imaging is generally conducted under anesthesia, as restriction of movements is necessary to avoid undesirable artifacts. Anesthesia is therefore one limitation for translational data, as studies in anesthetized animals have reported alterations in brain functioning and connectivity, cerebral blood, and inhibitory GABAergic neurotransmission (Gutierrez‐Barragan et al, 2022; Miranda et al, 2021; Ogawa et al, 2011; Prando et al, 2019). To avoid these limitations, some methodologies have been developed for evaluations in awake‐animals, such as performing scans using devices that restrict movement (Gutierrez‐Barragan et al, 2022; Mizuma et al, 2010; Suzuki et al, 2021) or using motion tracking and motion correction during image reconstruction (Miranda et al, 2019; Spangler‐Bickell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are also methodological constrains that might affect the translatability of findings from animal models to patients. For example, the use of anaesthetics in animal studies has been already identified as a confounding factor that can hamper the translatability of imaging studies [130][131][132]. Additionally, differences in the processing and quantification of the images can also debilitate the translatability of PET methods.…”
Section: Discussionmentioning
confidence: 99%
“…7 Translation of results from preclinical PET studies to human subjects can be compromised due to the additional use of anesthesia to perform preclinical PET scans. 8,9 For example, anesthesia has been shown to change the uptake of the glucose analog [ 18 F]FDG, as well as the binding of tracers targeting neurotransmitter receptors. 9 To circumvent the use of anesthesia in brain PET, motion correction methods have been developed to scan awake rodents.…”
Section: Introductionmentioning
confidence: 99%
“…9 To circumvent the use of anesthesia in brain PET, motion correction methods have been developed to scan awake rodents. 9 Particularly for mouse brain PET scans in freely moving animals, point source tracking with motion correction can be performed. 10…”
Section: Introductionmentioning
confidence: 99%